Malaysian People Financial Prosperity - Ismail, Fadillah; Ismail, Zuhaimy; Azhar Abd Hamid, Mohd.; Mohamad, Ismail; Abdul Kadir, Adibah; Thukiman, Kassim (International Journal of Engineering and Technology, 2018)
During the first sitting of the fifth term of the 13th Malaysian Parliament, The Yang di-Pertuan Agong Sultan Muhammad V pledged to reign in a just and fair manner by placing the well-being of the people and prosperity of the nation above all else.  Thus it becomes the task of the Malaysian Government which includes the financial prosperity of the people.  This paper aims at identifying the level of financial prosperity of Malaysian people.  It has been identified that financial prosperity is a major problems among Malaysians, a result obtained from a survey research with 2000 samples taken from the whole country which is in accordance with the standards set by the International Statistical Institute [ISI].  The data collected were analyzed using various statistical methods and one of the method used to determine the people financial prosperity or financial well-being is by using index, namely the Malaysian People Satisfaction Index [MPSI]. We categorized the financial prosperity into four levels, namely the poor income, moderate income, good income and excellent income. The survey results show that the level of financial prosperity for Malaysian people is 49.6% with a mean of 4.88 which is categorized as moderate income. Further analysis shows that there are significant differences between the respondents' demographic factors and the financial prosperity.  This shows that the government and relevant agencies need to play a more significant role to ensure the policies that are enacted can contribute to the well-being of the people.  It would just be very difficult for Malaysia to become a developed nation by 2020 if the status of financial prosperity or financial well-being of its people is still at moderate level income.